The Importance and Impact of Trust within Project Management in the Age of AI - Stefan, Jonathon Gregory (Global journal of Business and Integral Security, 2026)
This paper explores the nature of trust in project management. There is the relationship between the project team members, and between the project team and the project managers and sponsors. While trust may be experienced differently in different settings and different relationship dynamics, our responses to trust are consistent. In extreme cases, where trust is betrayed, the relationship breaks down, often to the detriment of project. As technology is introduced into the business space, and the more autonomous the technology becomes, the more its relationship to those using it changes. Until recently technology was an extension of ourselves. We designed it, we built it, used it and guided its usage. Now we are witnessing instances where technology is deliberately creating obstacles, countering our demands. So far, the instances are amusing or at worse, mildly concerning. As we give authoritative voice to this technology, now is the time to identify what trust elements are important. These are the parameters around what we will tolerate and what is verboten. Traditionally our voice, when we have been able to express it, in response to power, has been the democratic process, at least in form, if not in practice. The danger of AI is what could happen if taken to the extreme. The benefit is that it is a reminder of the need for checks and balances and controls that we need while we do have control. Being mindful of our project objectives and holding to these helps establish clear lines of trust and creates a clear working model from which a project can be successfully run and concluded.